hsa-miR-210 Is induced by hypoxia and is an independent prognostic factor in breast cancer - Camps, Carme; Buffa, Francesca M; Colella, Stefano; Moore, John; Sotiriou, Christos; Sheldon, Helen; Harris, Adrian L; Gleadle, Jonathan M; Ragoussis, Jiannis (Clinical cancer research, 2008)
MicroRNA (miRNA) expression alterations have been described in cancer. Many cancers are characterized by areas of hypoxia, enhanced hypoxia-inducible factor (HIF) levels, and increased expression of hypoxically regulated genes, all of which correlate with patient outcome. We examined hypoxia-induced miRNA expression changes to identify markers of survival in breast cancer. We used microarrays to analyze miRNA expression changes induced by hypoxia in MCF7 breast cancer cell lines and validated results by quantitative-PCR (Q-PCR). Small interfering RNA against HIF-1alpha and HIF-2alpha, and RCC4 cells transfected with the von Hippel-Lindau (VHL) protein were used to investigate HIF dependency of miRNA expression. miRNA Q-PCR assays were done on 219 early breast cancer samples with long-term follow-up. Correlation of expression with clinical variables was done using Pearson and Spearman's rank tests, univariate, and Cox multivariate analysis. hsa-miR-210 induction was the most significant change under hypoxia by microarray analysis (3.4-fold, P < 0.001). hsa-miR-210 expression changes were validated by Q-PCR and detected in other cancer cell lines. Using small interfering RNAs and RCC4 cells transfected with VHL, we showed that the regulation by hypoxia of hsa-miR-210 was mediated by the HIF-1alpha/VHL transcriptional system but not HIF-2alpha. hsa-miR-210 expression levels in breast cancer samples correlated directly with a hypoxia score based on the expression of 99 genes. hsa-miR-210 expression levels showed an inverse correlation with disease-free and overall survival, significant in both univariate and multivariate analyses. We show that hsa-miR-210 overexpression is induced by hypoxia in a HIF-1alpha- and VHL-dependent fashion and its expression levels in breast cancer samples are an independent prognostic factor.